SPEAKING TESTS AT TWO HIGHER EDUCATION INSTITUTIONS - Raynesa Noor Emiliasari (Journal of English Language Learning, 2021)
This study aims to investigate the preparation, administration, and scoring of the speaking tests. The study employed a case study design conducted in two higher education institutions in West Java. The data were gathered through document analysis of the syllabi to recheck the objective of the tests and the scoring rubrics, six classroom observations, semi-structured interviews with two lecturers, and open-ended questionnaires distributed to two lecturers. The findings indicated that the lecturers had been able to prepare the speaking tests based on the guidelines of the test preparation and the teaching objective in the institutions’ syllabus. But, the tests were in one-way communication, there were no interaction between the lecturers and the students.the lecturers also faced problems in the test administration: inadequate classroom facilities, limited time allocation, a relatively large number of students, the lecturers’ insufficient knowledge of the testing principles, and the vagueness of the scoring criteria. In addition, the lecturers had their own criteria in assessing the students’ performance: the first respondent focused on fluency, pronunciation and accuracy. The second one focused on fluency, pronunciation, grammar and content. Lastly, it was found that the lecturers gave one final score for each student because of the hassle they faced. The findings above suggest that the speaking lecturers need more ugrading in designing, administering and scoring the speaking tests in order to improve the administration of the tests. The speaking lecturers should be eager to widen their knowledge and develop the scoring criteria to give appropriate scores to the students. Key words: English speaking tests, test preparation, test administration, scoring.